A review of the sediment-hosted, disseminated precious metal deposits of Nevada : geological setting, classification, genesis and exploration - Ash, Philip John (Rhodes University, Faculty of Science, Department of Geology, 1986)
Carlin-type, fine-grained, "invisible" or Disseminated Replacement Type gold-silver deposits are all different names for a major new type of ore deposit that is currently being extensively developed in the Western United States. This type of deposit is now being found elsewhere. Thus a descriptive empirical model that emphasizes the geological and geochemical environment of formation is needed to assist the mining industry in the search for similar deposits. These deposits are typically formed in carbonaceous, silty dolomites and Iimestones or mineralization calcareous siltstones rocks and is exceedingly fine-grained is disseminated in the and claystones. host sedimentary Gold-silver , ore. Primary alteration usually less than one micron in size in unoxidized types include decalcification, argillitization, silicification resulting in the and pyritization. Silicification is commonly intense formation of jasperoid bodies which may be the host to higher grade ore. Supergene alteration is dominated by oxidation resulting in the formation of numerous oxides and sulphates and the release of gold from its association with sulphides and organic carbon. elements are As, Ba, Hg, Sb, and TI. Commonly associated trace Available geological, geochemical, fluid inclusion and stable-isotope studies lead to the conclusion that a circulating hydrothermal system is the important factor necessary for gold-silver concentration and deposition. A direct genetic or only casual relation between are deposition and discrete igneous formations remains unclear. However, it is considered that volcanism provided the source of heat necessary for the generation of a circulating hydrothermal system. High angle faults and fold structures facilitate transport and are of prime importance in directing are fluids to favourable host lithologies. The host rocks, overwhelmingly carbonate - rich, include those whose original and/or altered compositions and resulting permeability provide favourable sites for the precipitation of disseminated gold. The processes specialized. resulting Any th ick in the formation of these deposits are section of carbonate rocks has the potential not to produce Disseminated Replacement Type deposits wherever underlying igneous activity has developed a hydrothermal system
Keywords: Ore deposits